Стандардите за квалитет – маркетинг алатка за развој на претпријатијата од областа на прехранбената индустрија во Република Македонија и регионот на Западен Балкан - Шехаби, Ешија (Економски факултет, УКИМ, Скопје, 2018)
The main goal of this doctoral dissertation is to achieve a better understanding of the impact of quality standards in the modern marketing approach. This scientific work highlights the importance of implementation and the application of quality standards, because in the new circumstances (global market) they are emerging as one of тхе necessary marketing tools. Specific goals of this work are: - identifying the historical development of quality standards; - understand associations for the consumer and the enterprise when mentioning the quality standard; - identify quality strategies; - determining the ways in which marketing can be managed through quality standards; - revealing the meaning of the quality standards and their application in the food industry, especially in the Republic of Macedonia and the Western Balkan countries. The leading internationally accepted standards are described and the share they have, ie the scope of their use, with particular reference to the food industry. Apart from having an impact on getting a quality product, the quality of services and products has an impact on the enterprise and other market strategies in total. During the preparation of the dissertation, data were processed from enterprises that have acquired a certificate of quality. The results of these quantitative analyzes will serve as a tool for building marketing strategies in food businesses so that they can make decisions based on factual analysis.
Quality Standards, marketing tool for the development of food industry companies in the Republic of Macedonia and in the region of the Western Balkans
Докторска дисертација одбранета во 2018 година на Економскиот факултет во Скопје, под менторство на проф. д–р Снежана Ристевска Јовановска.
Keywords: quality, standard, marketing, management , organization